Symptomatic Benign Breast Cyst in a Young Male - Kheng, Hooi Chan; Wee, Yi Lim; Chang, Haur Lee; Siti Zubaidah Sharif; Firdaus Hayati; Nornazirah Azizan; Azlanudin Azman (Türkiye Klinikleri, 2022)
Simple breast cysts are benign lesions diagnosed in premenopausal women commonly presenting with a palpable breast lump. They are, however, extremely rare in males due to the absence of lobular tissue in the male breast. We report a case of a benign breast cyst in a 19-year-old male who presented with a left breast lump and nipple discharge. Clinical examination revealed a non-tender 2x2 cm mobile retro-areolar lump in the left breast with clear serous nipple discharge upon milking of the duct. Ultrasonography showed typical features suggestive of a simple breast cyst and fine needle aspiration cytology revealed epithelial cells of apocrine origin, thus confirming the diagnosis. We review the literature and discuss the approach to investigation of these uncommon lesions presented in males.